Does control of glycemia regulate immunological parameters in insulin-treated persons with type 1 diabetes? - Nekoua, P Magloire; Fachinan, Rufine; Fagninou, Adnette; Alidjinou, Enagnon Kazali; MOUTAIROU, KABIROU; Hober, Didier; YESSOUFOU, AKADIRI (My University, 2019)
Aims: We investigated the relationships between control of glycemia and the frequencies of immune cell subpopulations and also the profile of circulating T cell cytokines in insulin-treated persons with type 1 diabetes (T1D). Methods: Clinical data and blood samples were collected from two groups of persons with T1D exhibiting either adequate (AGC) or inadequate glycemic control (IGC), as well as from individuals without diabetes considered as a control group. Serum cytokine levels and immune cell subpopulation frequencies were determined. Results: Irrespective of their capacity to control glycemia, the percentages of effector CD4+ T-cells and CD19+ B-cells were higher in persons with T1D than in controls, whilst monocytes were significantly more frequent in those with IGC than in controls. The overall frequencies of CD4+ T-cells, CD8+ T-cells and Foxp3+CD4+CD25+ regulatory T-cells did not differ between the three groups. The serum levels of IL-2 and IFN-γ were lower in both groups with T1D compared to controls, whilst the level of IL-4 did not differ. The level of IL-10 was significantly lower in those with AGC compared to controls. Conclusion: Our study shows that insulin treatment is associated with a Th2-biased systemic immune phenotype in persons with T1D, reflected by a high proportion of effector CD4+ T cells and CD19+ B cells and a down-regulation of Th1-type serum cytokines
Keywords: Cytokines; Glycemic control; Immune cells; Insulin; Type 1 diabetes.